Students' Perspective on the Utilization of the Fluenday Application for Beginners to Improve Vocabulary - Fadhillah, Yoga; Salmiyah, Maryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore the use of the Fluenday application in enhancing English vocabulary mastery among senior high school students. Employing a qualitative approach through a case study method, the research involved 28 eleventh-grade students who actively used the Fluenday application over a four-week period, from which 10 participants were selected for in-depth interviews. Data were collected using a questionnaire consisting of 10 statements and a set of four semi-structured interview questions designed to reinforce the questionnaire findings and provide deeper insights into the learning activities within the application. Thematic analysis was used to interpret the data. The findings reveal that the use of Fluenday positively impacts students’ vocabulary acquisition. Students found it easier to learn new words through contextualized video clips and reported improved memorization through repetition-based features, personalized quizzes, and daily exercises. Moreover, students were motivated to engage with vocabulary learning due to the interactive interface and the gamified reinforcement system. Despite some challenges and dependencies such as limited access to premium features and reduced engagement with independent assignments due to reliance on the app, these obstacles did not significantly hinder the app’s overall effectiveness. Students agreed that these issues could be managed and did not obstruct their vocabulary improvement. Therefore, this study concludes that Fluenday can be considered an effective alternative medium for vocabulary learning, provided it is supported by consistent and well-targeted usage strategies. Keywords: Application, Enhancement of English Vocabulary Skills, Fluenday, Learning, Qualitative Research, Vocabulary.